The Effectiveness of Back Exercises for Chronic Low Back Pain Management Among Employees of PPMI Assalaam - Annisa Amalia; Arif Pristianto; Arin Supriyadi (P3M Universitas 'Aisyiyah Surakarta, 2026)
Background: Low Back Pain (LBP) is a highly prevalent musculoskeletal disorder, especially Chronic Low Back Pain (CLBP) that lasts for more than three months. The prevalence of low back pain among workers at PPMI Assalaam is very high and affects their functional abilities and work productivity. Risk factors for CLBP include age, body mass index, duration of sitting, and static and repetitive workloads. Purpose: This study aims to evaluate the effect of modified back exercises based on a combination of the McKenzie method and core stability exercises in the form of rhythmic gymnastics with music on reducing pain intensity and improving functional ability in employees with CLBP. Method: This study used a pretest-posttest quasi-experimental design with a sample of 50 employees. The experimental group performed back exercises three times a week for one month, while the control group only received education through posters. Pain intensity was measured using the Visual Analog Scale (VAS) and functional ability using the Oswestry Disability Index (ODI) before and after the intervention. Conclusion: Modified back exercises effectively reduce CLBP pain, improve function, and enhance employees' quality of life. These exercises are easy to implement and encourage consistency in preventing work-related back pain.